1933
DOI: 10.1121/1.1915608
|View full text |Cite|
|
Sign up to set email alerts
|

On Minimum Audible Sound Fields

Abstract: The minimum audible field (M.A.F.) has been determined from data taken on 14 ears over the frequency range from 100 to 15,000 c.p.s. The observer is placed in a sound field which is substantially that of a plane progressive wave, facing the source and listening monaurally. The M.A.F. is expressed as the intensity of the free field, measured prior to the insertion of the observer. Similar data are presented for binaural hearing, over the range from 60 to 15,000 c.p s., obtained with 13 observers. At 1000 c.p.s.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1955
1955
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 260 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…Though the differences are generally greater at frequencies <1 kHz, frequencies >8 kHz show the greatest variability in 3 cases and in 1 case frequencies between 1 and 8 kHz are most variable. The low-frequency (<1 kHz) results agree with the findings of Jackson et al (1999), but go further to show that all regions of the audiogram are affected by transducer type, similar to the conclusions reached by Sivian and White (1933). Packer (1983) suggested that using headphones may cause physiological noise partially to mask frequencies <1 kHz, resulting in auditory thresholds with higher sound pressure levels.…”
Section: Effects Of Transducer Type and Conditioning Proceduressupporting
confidence: 86%
See 4 more Smart Citations
“…Though the differences are generally greater at frequencies <1 kHz, frequencies >8 kHz show the greatest variability in 3 cases and in 1 case frequencies between 1 and 8 kHz are most variable. The low-frequency (<1 kHz) results agree with the findings of Jackson et al (1999), but go further to show that all regions of the audiogram are affected by transducer type, similar to the conclusions reached by Sivian and White (1933). Packer (1983) suggested that using headphones may cause physiological noise partially to mask frequencies <1 kHz, resulting in auditory thresholds with higher sound pressure levels.…”
Section: Effects Of Transducer Type and Conditioning Proceduressupporting
confidence: 86%
“…Both comparisons suggest that the conditioning procedure only marginally affects the auditory thresholds. Sivian and White (1933) first documented differences produced by different transducer types in their classic study on human hearing. They noted that thresholds produced by loudspeakers were consistently lower throughout the entire frequency range than those produced using headphones.…”
Section: Previous Research On Procedural Differencesmentioning
confidence: 98%
See 3 more Smart Citations